LEGAL ASPECTS OF THE FOURTH INDUSTRIAL REVOLUTION (4iR) – (with specific reference to ChatGPT and other software purporting to give Legal Advice) - DP van der Merwe (Obiter, 2024)
In the present article, the author explains the tremendous impact that Artificial Intelligence (AI) is likely to have on society in general. After a historical overview that covers the Fourth Industrial Revolution, the article also considers how the various legal disciplines are likely to be affected by the arrival of AI. This includes an evaluation of the legal advice likely to be given by new “experts” from these two disparate fields.